معالجة الإشارات كمتجهات في الفراغ الإتجاهي متعدد الأبعاد - عبود سميرة (Latakia University Journal -Engineering Sciences Series, 2018)
This research shows how signals can be treated as vectors in multi-dimensional directional vacuum. So that it can apply the Equations and concepts known in spherical geometry in the analysis and signal processing in communications systems. And the research shows how to conclude any power signal of a group of assumed signals (Vectors) in directional vacuum, and by devising linear approximation for the signal to be obtained in accordance to criterion of the least squares errors, and assumed that signals are non-reciprocall yorthogonal as in the case of analyzing signal according to Fourier transform which contains the infinite number of orthogonal harmonics, where the number of those signals are limited. يعرض هذا البحث كيف يمكن معالجة الإشارات كمتجهات في الفراغ الاتجاهي متعدد الأبعاد بحيث يمكن تطبيق العلاقات والمفاهيم المعروفة في الهندسة الفراغية في تحليل ومعالجة الإشارة وفي نظم الاتصالات, ويقوم البحث باستنتاج أي إشارة قدرة من مجموعة من الإشارات المفترضة(المتجهات) الموجودة في الفراغ الاتجاهي وذلك باستنباط تقريب خطّي للإشارة المراد الحصول عليها وفق معيار أقل تربيعات الأخطاء, والإشارات المفترضة غير متعامدة تبادلياً كما هو الحال عند نشر الإشارة وفق منشور فوريير الذي يحوي على عدد لانهائي من التوافقيات المتعامدة,حيث عدد هذه الإشارات محدود.